2012
DOI: 10.1136/bjophthalmol-2011-300551
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopic findings in patients with limbal stem cell deficiency

Abstract: A number of features were demonstrated by laser IVCM in patients presenting clinically with LSCD. Some of these features were corroborated with features observed on histological examination of tissue samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 38 publications
5
46
0
17
Order By: Relevance
“…32 The corneal or conjunctival epithelial transition zone and cellular phenotype as revealed by IVCM have also been shown in correlation with the presence or absence of the POV in LSCD. 33,34 In another series of LSCD patients, IVCM was used to examine the POV and limbal epithelium in early, intermediate, and late clinical stages of LSCD, where one could see that the POV were completely degraded at the early stage. 35 The above studies examined LSCD as a heterogeneous group, often with only one or two aniridia patients included.…”
Section: The Limbal Stem Cells and The Stem Cell Nichementioning
confidence: 99%
See 1 more Smart Citation
“…32 The corneal or conjunctival epithelial transition zone and cellular phenotype as revealed by IVCM have also been shown in correlation with the presence or absence of the POV in LSCD. 33,34 In another series of LSCD patients, IVCM was used to examine the POV and limbal epithelium in early, intermediate, and late clinical stages of LSCD, where one could see that the POV were completely degraded at the early stage. 35 The above studies examined LSCD as a heterogeneous group, often with only one or two aniridia patients included.…”
Section: The Limbal Stem Cells and The Stem Cell Nichementioning
confidence: 99%
“…41 In humans, IVCM has been used to quantify subbasal epithelial nerves in LSCD, where a markedly reduced nerve density has likewise been found in a case series without aniridia patients 35 and in a series including two aniridia patients. 34 In a Swedish cohort of 16 aniridia subjects where IVCM was used, a wide range of subbasal nerve density was reported, including 3 patients with abnormally high innervation of the central cornea. 29 Nerve patterns were disrupted, and esthesiometry indicated that corneal touch sensitivity was reduced below normal levels in 5 of 14 patients.…”
Section: Corneal Nervesmentioning
confidence: 99%
“…In the past, LSCD diagnosis rested primarily on history and clinical signs 1 , with confirmation by histology 2 and impression cytology. 3 With the advent of in vivo laser scanning confocal microscopy (IVCM), live imaging of the corneo-limbal epithelial architecture in healthy individuals [4][5][6][7] and LSCD patients 2,3,8 became possible. Confirmation of loss of palisades of Vogt (POV) and conjunctivalization by IVCM is now an adjuvant to diagnose LSCD.…”
Section: Introductionmentioning
confidence: 99%
“…IVCM scanning in the above studies focused on the POV [2][3][4][5][6][7][8] in the limbus, but not the microarchitecture of the limbal stroma. Recent studies using human cadaver tissue examined the cellular components of the anterior limbal stroma and their role in the maintenance of stemness in the basal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Zmniejsza się gęstość komórek podstawnych nabłonka, a jednocześnie zwiększają ich wymiary. W obrazie mikroskopowym możliwe jest również zidentyfikowanie komórek kubkowych spojówki, jednak ich obecność nie jest jednoznaczna z występo-waniem LSCD [68].…”
Section: Choroby Rąbka Rogówki Związane Z Niedoborem Lescunclassified